2005
DOI: 10.1093/bja/aei030
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind comparison of intrapleural saline and 0.25% bupivacaine for ipsilateral shoulder pain after thoracotomy in patients receiving thoracic epidural analgesia

Abstract: Intrapleural administration of 40 ml of bupivacaine 0.25% does not provide effective pain relief for ipsilateral post-thoracotomy shoulder pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 25 publications
1
44
1
Order By: Relevance
“…The 86% prevalence of PTSP, amongst all patients in this study, is within the 60% to 97% range of that reported in recent literature. [3][4][5][6] This confirms that most post-thoracotomy patients will experience shoulder pain in the early postoperative period.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The 86% prevalence of PTSP, amongst all patients in this study, is within the 60% to 97% range of that reported in recent literature. [3][4][5][6] This confirms that most post-thoracotomy patients will experience shoulder pain in the early postoperative period.…”
Section: Discussionsupporting
confidence: 55%
“…Patients complain of a constant, moderate to severe, aching pain, in the posterior deltoid and in the suprascapular region, ipsilateral to the surgery. [1][2][3][4][5][6] The most plausible mechanisms, amongst several proposed to explain the occurrence of post-thoracotomy shoulder pain (PTSP), 2,7,8 appear to be pain referred from an irritation of the pericardium or pleural surfaces. 5 Different pharmacological agents have been used to alleviate PTSP, but few of these modalities have proven attractive, notably because of their side effects and their relatively short half-life.…”
mentioning
confidence: 99%
“…Intrapleural bupivacaine did not provide effective pain relief (56). Superficial cervical plexus or interscalene brachial plexus blocks effectively reduced localized shoulder pain in some patients (57;58), whereas suprascapular nerve block was not helpful (59).…”
Section: Shoulder Painmentioning
confidence: 95%
“…As regards concentration, 0.25% bupivacaine showed to be effective in cholecystectomies when compared to a similar volume in concentrations of 0.375% and 0.5% Most studies show lesser worsening in respiratory function after the intrapleural block 12,34 ; others also affirm that the ventilatory parameters cannot be used as predictors for postoperative complications 35 . What is known is that, clinically, the intrapleural block does not determine adverse effects in the respiratory muscle function and, contrarily, it becomes beneficial due to reduced postoperative pain…”
Section: Resultsmentioning
confidence: 99%